Zinc and cadmium complexes of a plant metallothionein under radical stress: desulfurisation reactions associated with the formation of trans-lipids in model membranes. - Torreggiani, Armida; Domenech, Jordi; Orihuela, Ruben; Ferreri, Carla; Atrian, Silvia; Capdevila, Merce; Chatgilialoglu, Chryssostomos (Chemistry (Weinheim an der Bergstrasse, Germany), 2009)
Metallothioneins (MTs) are sulfur-rich proteins capable of binding metal ions to give metal clusters. The metal-MT aggregates used in this work were Zn- and Cd-QsMT, where QsMT is an MT from the plant Quercus suber. Reactions of reductive reactive species (H(*) atoms and e(aq)(-)), produced by gamma irradiation of water, with Zn- and Cd-QsMT were carried out in both aqueous solutions and vesicle suspensions, and were characterized by different approaches. By using a biomimetic model based on unsaturated lipid vesicle suspensions, the occurrence of tandem protein/lipid damage was shown. The reactions of reductive reactive species with methionine residues and/or sulfur-containing ligands afford diffusible sulfur-centred radicals, which migrate from the aqueous phase to the lipid bilayer and transform the cis double bond of the oleate moiety into the trans isomer. Tailored experiments allowed the reaction mechanism to be elucidated in some detail. The formation of sulfur-centred radicals is accompanied by the modification of the metal-QsMT complexes, which were monitored by various spectroscopic and spectrometric techniques (Raman, CD, and ESI-MS). Attack of the H(*) atom and e(aq)(-) on the metal-QsMT aggregates can induce significant structural changes such as partial deconstruction and/or rearrangement of the metal clusters and breaking of the protein backbone. Substantial differences were observed in the behaviour of the Zn- and Cd-QsMT aggregates towards the reactive species, depending on the different folding of the polypeptide in these two cases.
Keywords: biomimetic chemistry; liposomes; metalloproteins; radical reactions; reaction mechanisms